Entre fenomenologia e lógica: o conceito hegeliano do absoluto - Baioni, José Eduardo (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: The aim of this paper is to investigate how the concept of the Absolute (das Absolute) was designed and exposed by Hegel in two of his major works. Our interpretative hypothesis is that the way in which Hegel uses this concept in a phenomenological framework – namely, the way in which this concept is set out in the Introduction of the Phenomenology of Spirit (1807) and developed in the figures of consciousness of Spirit, from the sensible consciousness to self-consciousness as the ‘absolute Knowledge’ –, partly anticipates various other uses which will be discussed within the first part of the Encyclopedia of the Philosophical Sciences (1830), the Science of Logic. In this book, the exposition of the logical categories within pure thought made it necessary to anticipate that all logical determinations are ‘definitions of the absolute’ or ‘metaphysical definitions of God.’